Self-system and mental health status among Malaysian youth attending higher educational institutions: a nationwide cross-sectional study - Mohamad, Fadzilah; Azlan, Syifa'; Dahlan, Rahima; Ismail, Irmi Zarina; Kadir, Hayati; Kamaruddin, Khairatul Nainey; Shibraumalisi, Nur Amirah; Syed Mohamad, Sharifah Najwa; Shamsuddin, Nurainul Hana (Academy of Family Physicians of Malaysia, 2024)
Introduction: Mental health disorders (MHDs) are a global health burden with an increasing prevalence. During the COVID-19 pandemic, depression was the commonest MHD, followed by anxiety and stress. This nationwide study aimed to determine the prevalence and associated factors of depression, anxiety and stress among Malaysian students attending higher educational institutions. Methods: A cross-sectional study was conducted from June to December 2021. Institutions were selected via stratified random sampling and students via convenience sampling. A self-administered questionnaire comprising questions on socio-demographic characteristics, academic background, substance abuse, childhood abuse, religiosity and the Depression Anxiety Stress Scale-21 was used. Data were analysed using SPSS version 27; descriptive, point-biserial correlation, chi-square and multiple binary logistic regression analyses were conducted. Results: Sex and adverse childhood experiences significantly predicted all three MHDs (P<0.05). The students from public institutions (odds ratio [OR]=0.71, 95% confidence interval [CI]=0.56–0.90, P=0.004) had a lower risk of depression than those from private institutions. The smokers/vapers (OR=1.43, 95% CI=1.02–2.02, P=0.041) a higher risk of depression than the non-smokers/non-vapers. The social science students (OR=1.29, 95% CI=1.01–1.65, P=0.039) had a higher risk of anxiety than the science students. The students who highly engaged in organisational religious activity (OR=0.91, 95% CI=0.84–0.98, P=0.015) had a lower risk of anxiety than their counterparts. Conclusion: Anxiety is the commonest MHD among Malaysian youth, followed by depression and stress. Childhood abuse is a crucial related factor requiring further attention. Screening, surveillance, preventive measures and comprehensive interventions for MHDs should be initiated among youth.